Antioxidant and skin-whitening effects of aerial part of Euphorbia supina Raf. Extract - Sa-Haeng Kang; Yong-Deok Jeon; Ji-Yoon Cha; Sung-Woo Hwang; Hoon-Yeon Lee; Min Park; Bo-Ri Lee; Min-Kyoung Shin; Su-Jeong Kim; Sang-Min Shin; Dae-Ki Kim; Jong-Sik Jin; et al. (BMC, 2018)
Abstract Background Euphorbia supina (ES) has been widely used in folk medicine owing to its antibacterial, hemostatic, and anti-inflammatory properties. The aim of this study was to evaluate the antioxidant and skin-whitening effects of a 70% ethanol extract of ES. Methods The aerial parts of ES plant were extracted with 70% ethanol. The viability of B16F10 cells was evaluated by MTT assay to determine the non-toxic doses for further experiments. The tyrosinase and cellular tyrosinase activities were then measured using an enzyme-substrate assay. In addition, the expression of whitening-related proteins was measured using western blot. Results The antioxidant activity of the ES samples increased in a dose-dependent manner, as confirmed by their radical scavenging activities in the 2,2-diphenyl-1-1-picrylhydrazyl and 2,2-azino-bis-(3-ethylbenzthiazoline-6-sulfonic acid) assays. The ES extract significantly reduced tyrosinase activity and melanin content in a dose-dependent manner. Furthermore, it decreased α-melanocyte stimulating hormone (MSH)-induced protein expression of tyrosinase and microphthalmia-associated transcription factor (MITF). Conclusions Our results indicate that the ES extract attenuated α-MSH-stimulated melanin synthesis by modulating tyrosinase and MITF expression. Therefore, the ES extract could be a promising therapeutic agent to treat hyperpigmentation and as an ingredient for skin-whitening cosmetics.